Development of Blockchain-Based Digital Signature Platform - Ang Sandy Kristiawan; F Ridwan Sanjaya; FX Hendra Prasetya (Journal of Business and Technology, 2022)
As technology develops, the Internet of Things (IOT) becomes a topic that is being mentioned over and over again. Many things can be done online. One of them is document signing activity. A company named “XYZ” wanted to build a prototype application using a framework that can build and develop a multiplatform app that can be used to sign a document and secure it with digital certificates, and the transaction activity is recorded and can be verified through a blockchain system. This study aims to find out how to apply blockchain system in a series of digital signing activities, how are the concept and how to verify a transaction that already recorded in a blockchain system, and also how to make a prototype that easy to develop further for other platforms. In the end, the application can be made easily using Expo, Node.Js, and the process for recording and verifying transactions can be done easily with the help of Hyperledger Iroha.